Leading Change, Internal Communication and Change Management in the University Environment - Ahmad, Hartini; Mohd Nafi, Siti Noratisah; Marchalina, Leonis (2018)
Change is assumed as a challenge that most of organisations confront regardless their types of business and sizes. Hence, the leading change and internal communication are very significant in the change management context.This paper aims to provide an understanding on the change management in the university based on the leadership and internal communication factors. This paper is based on the survey questionnaires sent to the employees in the selected university. Other than that the qualitative approach was conducted by interviewing the selected participants for the study.The paper indicates the effective leadership and communication for change were associated to the change management commitment.Furthermore, the moderating effect of the internal communication is very significant in the change implementation by the leader of the university.The paper is hoped to contribute to the body of knowledge in terms of the subject matter in a university setting. The paper’s main contribution is making explicit on both top management’s and employees’ factors on the change management to guide the university to meet the desirable results, as well as to ensure the business sustainability.